A Patient Specific Biomechanical Analysis of Custom Root Analogue Implant Designs on Alveolar Bone Stress: A Finite Element Study - David Anssari Moin; Bassam Hassan; Daniel Wismeijer (International Journal of Dentistry)
Objectives. The aim of this study was to analyse by means of FEA the influence of 5 custom RAI designs on stress distribution of peri-implant bone and to evaluate the impact on microdisplacement for a specific patient case. Materials and Methods. A 3D surface model of a RAI for the upper right canine was constructed from the cone beam computed tomography data of one patient. Subsequently, five (targeted) press-fit design modification FE models with five congruent bone models were designed: “Standard,” “Prism,” “Fins,” “Plug,” and “Bulbs,” respectively. Preprocessor software was applied to mesh the models. Two loads were applied: an oblique force (300 N) and a vertical force (150 N). Analysis was performed to evaluate stress distributions and deformed contact separation at the peri-implant region. Results. The lowest von Mises stress levels were numerically observed for the Plug design. The lowest levels of contact separation were measured in the Fins model followed by the Bulbs design. Conclusions. Within the limitations of the applied methodology, adding targeted press-fit geometry to the RAI standard design will have a positive effect on stress distribution, lower concentration of bone stress, and will provide a better primary stability for this patient specific case.